Using linear polarization to monitor nanoparticle purity. (September 2015) - Barreda, Ángela I.; Sanz, Juan M.; Alcaraz de la Osa, Rodrigo; Saiz, José M.; Moreno, Fernando; González, Francisco; Videen, Gorden
Abstract: We study the effect of contaminants on the resonances of silicon nanoparticles (NPs) by considering the spectral evolution of the degree of linear polarization of light scattered at right angles to the incident beam, P L ( 90 ° ) . From an optical point of view, a decrease in the purity of silicon nanoparticles due to the presence of contaminants impacts the NP effective refractive index. We analyze this effect for a silicon nanosphere ( R =200 nm) suspended in different media. We focus on the spectral range where the quadrupolar magnetic, dipolar electric and dipolar magnetic resonances appear. The weakness of the resonances induced on the P L ( 90 ° ) spectrum by the lack of purity can be used to quantify the contamination of the material. In addition, it is shown that Kerker conditions also suffer from a spectral shift, that is quantified as a function of material purity. Abstract : Highlights: We study the effect of contamination on nanoparticle resonances. We compare linear polarization with extinction as a measurement tool. Contamination weakens the resonances and changes the Kerker conditions.